Metabolic stress activates an ERK/hnRNPK/DDX3X pathway in pancreatic β cells - Austin L. Good; Matthew W. Haemmerle; Alexis U. Oguh; Nicolai M. Doliba; Doris A. Stoffers (Elsevier, 2019)
Objective: Pancreatic β cell failure plays a central role in the development of type 2 diabetes (T2D). While the transcription factors shaping the β cell gene expression program have received much attention, the post-transcriptional controls that are activated in β cells during stress are largely unknown. We recently identified JUND as a pro-oxidant transcription factor that is post-transcriptionally upregulated in β cells during metabolic stress. Here we seek to uncover the mechanisms underlying this maladaptive response to metabolic stress. Methods: RNA-protein and protein-protein interactions were measured using RNA immunoprecipitation and co-immunoprecipitation, respectively, in Min6 cells and mouse islets. Phos-tag analyses were used to assess hnRNPK phosphorylation in primary mouse and human islets and Min6 cells. Translating ribosome affinity purification (TRAP) followed by RT-qPCR was used to identify changes in the ribosome occupancy of mRNAs in Min6 cells. Gene depletion studies used lentiviral delivery of CRISPR-Cas9 to Min6 cells. Apoptosis was measured in primary islets using a cell-permeable dye with a fluorescence readout of activated cleaved caspase-3 and-7. Results: A de novo motif analysis was performed on a subset of genes previously found to be regulated at the level of ribosome binding during PDX1-deficiency, which identified a poly-cytosine (polyC) motif in the 3'UTR of the transcript encoding JUND. The polyC-binding protein hnRNPK bound to the mRNA encoding JUND, leading us to hypothesize that hnRNPK regulates JUND expression during glucolipotoxicity. Indeed, loss of hnRNPK blocked the post-transcriptional upregulation of JUND during metabolic stress. hnRNPK was phosphorylated in mouse and human islets during glucolipotoxicity and in islets of diabetic db/db mice. The MEK/ERK signaling pathway was both necessary and sufficient for the phosphorylation of hnRNPK, upregulation of JUND levels, and induction of pro-oxidant and pro-inflammatory genes. Further, we identified the RNA helicase DDX3X as a new binding partner for hnRNPK that is required for efficient translation of JUND mRNA. Loss of hnRNPK reduced DDX3X binding to translation machinery, suggesting that these factors cooperate to regulate translation in β cells. Conclusions: Our results identify a novel ERK/hnRNPK/DDX3X pathway that influences β cell survival and is activated under conditions associated with T2D. Keywords: RNA-Binding proteins, β cell, Stress, Translational regulation, Signaling